Revolutionizing the legislative process through a knowledge management system a strategy of the committee affairs Department House of Representatives - Amorin, David Robert U.; Talisayon, Serafin D. (Quezon City University of the Philippines Diliman, 2005)
"Knowledge is the information useful for effective and efficient action". It is considered by KM practitioners as the "know-how" as differentiated from information/data which is "know-what". Knowledge then is essential to information since knowledge is "what-works" and information as "what is". Peter Drucker in "The New Realities" stated that "Knowledge is information that changes something or somebody-either by becoming grounds for action, or by making an individual (or an institution) capable of different or more effective action". Laurence Prusak, Executive Director of IBM Institute for Knowledge Management, speaks of a continuum of knowledge ranging from 'capture' at one end to 'connectivity' at the other. Arian Ward, of Work Frontiers International describes knowledge management as : "It's not about creating an encyclopaedia that captures everything that anybody ever knew. Rather, it's about keeping track of those who know the recipe, and nurturing the culture and technology that will get them talking." The aim of this paper is three-fold : 1. To conduct a thorough review and assessment on the Committee Affairs Department of the House of Representatives' (CAD-HOR) knowledge management maturity level by using the Gaps Analysis Method; 2. To develop a strategy for a systematic approach to successfully implementing Knowledge Management (KM), tailoring said KM tools and practices to the specific needs and goals of the department; and 3. To come up with a User's Guide for the initial version of the Committee Bills Monitoring System (CBMS) that allows the integration of committee information/status with the Legislative Information System (LEGIS). The above purpose including the project output/s that the study generated will ensure accuracy, transparency, accountability, timeliness, and comprehensive coverage of information that will aid the HOR Leadership and its Members including the career and permanent secretariat officials in formulating policies and legislative measures. This endeavor will only tackle the mandate of CAD's role in legislative making process. However, other departments within the House of Representatives (HOR) such as the Legislative Operations Department particularly the Plenary Affairs Bureau, and the Reference and Research Bureau will also be slightly touched in terms of the collaboration currently being done relative to the legislative law-making processes. Close coordination also with the Knowledge Management Systems Bureau (KMSB) of the HOR and the Information and Technology Service (ICTS) were made not only to inform them of the study being done but also to integrate the proposals, if possible to the whole KM System of the HOR thereby giving it a holistic approach on the knowledge capture and knowledge sharing scheme conducted by the CAD and its users. Knowledge Management and Information Technology is considered one of the strategic components of the National Information Technology Plan that contains the objectives, strategies, programs and projects pertinent to the development of knowledge management and information technology use in the government. In order for government to better respond to the requirements of public service, there is a need to significantly improve knowledge management and information systems. With increased complexity, volume of data and the need for timely and accurate information, knowledge management and information technology furthers the gains that can be made in having a good information system. In government as a whole, the objectives of utilizing KM and IT tools and practices are the following, to wit : (1) to improve delivery of government services to the people; (2) to increase the government's capability for coordination, planning, policy formulation and implementation of this development programs and projects; and (3) to promote transparency in government transactions. Being the legislative arm of our government, these objectives must be incorporated in the House of Representative's (HOR) mission to continuously improve the law-making process and its support functions-through a constantly evolving information technology and knowledge management practices. As such, there is a never-ending need to adapt to changing environment and the HOR Knowledge Management System should be developed and enhanced to be flexible to support both changes in the political, economic and social environment and the changes in technology. A good HOR KM System is one that provides : (1) relevant and timely knowledge and information that is responsive, open and receptive to its clients, (2) accurate, complete and transparent knowledge and information that is accessible by the public; and (3) accountable knowledge and information where the source of information is patent and traceable backed with solid evidentiary basis. The Knowledge Management System (KM System) of an organization should serve the goals and mandates of the organization. The KM System strategic framework, design and operation should be given by organizational goals. The link between KM and organizational goals is through the functions and processes mandated for the organization (Talisayon, Gaps Analysis, 2005) : KM System - Functions and Key Processes - Desired Organizational Results. All these taken into consideration, this study evaluated the people, culture, politics and other factors impacting the CAD's knowledge management system. Through such an assessment, CAD not only identified the purpose of the KM system, but also defined its relationship to the HOR organization's strategic vision and communicated the desired outcome to the appropriate parties. However, considering the diversity of the jurisdiction of different Committees within the CAD, from investigations in aid of legislation of Dual Citizenship Law, Automation in the Elections, e-Commerce and possible legislation of the Cybercrime, the documents to be surveyed and studied including the drafters of said legislation and its work environment will be limited only to the 12th Congress (July 2001 to May 2004), and the present 13th Congress First Regular Session (July 2004 to May 2005).
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: House of Representatives; Legislation; Knowledge management